2020
DOI: 10.1016/j.jseaes.2019.104106
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircons from Late Paleozoic to Triassic sedimentary rocks of the Gongshan-Baoshan Block, SE Tibet: Implications for episodic crustal growth of Eastern Gondwana

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The zircon grains with U–Pb ages <500 Ma largely retain oscillatory zoning and show euhedral to subhedral shape, indicating a magmatic origin and short‐distance provenance. The age of the oldest rock mass found in the Baoshan Block is 502–459 Ma (Dong, 2016; Li et al, 2016; Liu et al, 2009; Song et al, 2007; Song et al, 2020). Farther to the south, the Khuu Tao orthogneiss and the Khao Dat Fa granite yield concordant ages of 501 Ma and 477 Ma, respectively, in northern Peninsular Thailand (Kawakami et al, 2014; Lin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The zircon grains with U–Pb ages <500 Ma largely retain oscillatory zoning and show euhedral to subhedral shape, indicating a magmatic origin and short‐distance provenance. The age of the oldest rock mass found in the Baoshan Block is 502–459 Ma (Dong, 2016; Li et al, 2016; Liu et al, 2009; Song et al, 2007; Song et al, 2020). Farther to the south, the Khuu Tao orthogneiss and the Khao Dat Fa granite yield concordant ages of 501 Ma and 477 Ma, respectively, in northern Peninsular Thailand (Kawakami et al, 2014; Lin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…10). Detrital zircon U-Pb ages of the Triassic sediments of the Sibumasu Block in SW China (Gongshan-Baochan Block) have representative peaks for 2500-2400 Ma, 1750-1500 Ma, 1200-900 Ma, 600-500 Ma, and very few Permian zircons (Song et al 2020), presenting similar peak composition to those of the Mae Sariang Group. The Upper Triassic to Lower Jurassic sediments of the Sibumasu Block in eastern Myanmar (Loi-an Group) adjacent to NW Thailand show a pronounced 1900-1800 Ma peak (Cai et al 2017), correlating with the Lesser Himalayan igneous event, and less clear peaks of 1000-900 Ma and 600-500 Ma, corresponding to the Grenville and Pan African orogenies, respectively.…”
Section: C Sibumasu Block and Permian-triassic Hiatus In Igneous Activitymentioning
confidence: 97%
“…The U-Pb age spectra of these detrital zircons have been shown to differ between microcontinents, meaning that the spectra are useful for distinguishing the sediment provenance, basement erosion, sediment transportation and palaeogeography of each microcontinent. Detrital zircon U-Pb age spectra have been obtained from Triassic sediments of the Indochina Block in Thailand (Arboit et al 2016b;Yan et al 2017), the Sibumasu Block in eastern Myanmar (Cai et al 2017) and southwestern China (Song et al 2020), and the South China Block in southern China (Hu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Paleo-Tethys Ocean separated the European and Asiatic Hunic terranes and Gondwana (Metcalfe, 2013;Zhao et al, 2018a). Several studies have suggested that the Paleo-Tethys Ocean started to open in the Devonian, and its final closure occurred at ~220 Ma (Jian et al, 2009;Zhai et al, 2011Zhai et al, , 2013Song et al, 2020). The tectonic evolution of the Proto-and Paleo-Tethys oceans clearly played key roles in the assembly of the East Asian blocks in Pangea (Li et al, 2018;.…”
Section: Introductionmentioning
confidence: 97%